Molecular orientation controlled by few-cycle phase-jump pulses. (7th December 2017) - Ma, Ling; Chai, Shuo; Zhang, Xiao-Miao; Yu, Jie; Cong, Shu-Lin
Abstract: A theoretical scheme used for controlling efficiently molecular orientation with a few-cycle phase-jump pulse is proposed, with the LiH molecule as an example. It is shown that the molecular orientation can be greatly enhanced by applying this scheme compared to the few-cycle pulse. By optimizing the laser parameters, a high degree of molecular orientation 0.860 is obtained at temperature T = 0   K . Furthermore, by changing the jump phase and the electric field amplitude of few-cycle phase-jump pulse, the molecular orientation can be improved to some degree. The effect of temperature on molecular orientation is also discussed, the degree of molecular orientation decreases with the increase of temperature.